Legal Protection for Health Workers Working in Remote Areas : Research Study in Kapuas Hulu Regency - Ismawan Adrianto; Sumarno Sumarno; T Riza Zarzani (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
This research examines the implementation of legal protection for healthcare workers serving in remote areas, with a case study in Kapuas Hulu Regency. The main focus of the study is to analyze the effectiveness of existing legal protections and identify factors hindering their implementation. Through a qualitative approach using case study methods, this research reveals a significant gap between existing regulations and practices in the field. The case of Dr. I serves as a concrete example of weak legal protection, ranging from transfers without adequate consideration to eviction from official residences. Identified inhibiting factors include lack of understanding among local officials, weak inter-agency coordination, and discrepancies between central policies and local implementation. This study recommends the need for comprehensive reform in the legal protection system for healthcare workers in remote areas, including capacity building for local officials and strengthening oversight mechanisms.